Brain Tumour Lessons From Alzheimer's Disease: Beta-Amyloid and SorLA Expression in Glioblastoma. (1st October 2022) - Jones, Lydia; Jones, Vicky; Shaw, Lisa; Stasik, Izabela; Smith, Christopher
Abstract: AIMS: Exploring how two proteins strongly associated with Alzheimer's disease are expressed in glioma. Amyloid beta (Aβ) is a peptide cleaved from amyloid precursor protein (APP) that is shuttled around the cell by sorting-related receptor with A-type repeats (SorLA). Low expression of SorLA has been linked to increased risk of Alzheimer's disease as APP processing shifts towards production of the plaque-forming Aβ42 rather than the more benign Aβ40. METHOD: Expression of Aβ40, Aβ42 and SorLA was determined in immortalised cell lines (grade 4 glioblastoma U87MG, grade 2 astrocytoma 1321N1, foetal astrocytes SVGp12), glioblastoma patient-derived cells (PD301, PD304) and normal human astrocytes through western blotting or immunocytochemistry. RESULTS: SorLA was present in all cells. Relative optical density was more than 60-fold higher for U87MG glioblastoma cells and approximately 10-fold higher for 1321N1 astrocytoma cells than SVGp12 cells. Similarly, SorLA had a significantly higher expression (p<0.01) in patient derived cells than normal human astrocytes. High expression of SorLA was accompanied by lower Aβ42 in patient derived cells compared to normal human astrocytes. Expression of Aβ40 was similar across patient derived cells and normal human astrocytes. CONCLUSION: These data suggest that SorLA is retained in glioblastoma and remains functional to drive APP processing away from Aβ42 production. Future work will determine how high SorLA expression contributes to the increased motility and invasiveness seen in glioblastoma cells by transfecting siRNA to knock down SorLA.